Implementasi Penyusunan Bahan Ajar Otentik Berbasis Media Sosial bagi Guru Bahasa Sunda di Kabupaten Pangandaran - Dingding Haerudin; Dedi Koswara; Danan Darajat (Universitas Pendidikan Indonesia, 2021)
This Community Service (PkM) is motivated by the lack of authentic learning media for Sundanese subjects. Types of media in learning Sundanese including factual, conceptual, principal, and procedural. Recently, it was difficult for teachers to implement the type of factual material. It was caused by unskilled factor on processing learning materials in the Curriculum 2013 Revised 2017 based on competency basis and competency core (KIKD) of Mulok Sundanese Language with authentic materials in authentic learning. Based on the analysis of the situation that became the background of the problem, the purpose of this community services was to improve the skills of selecting and compiling authentic learning materials for Sundanese language teachers in Pangandaran Regency. The methods of this community services were hybrid learning with explanation, question and answer, and workshop techniques. The target is teachers as members Teacher Working Group (MGMP) of Sundanese language in junior high schools and senior high schools in Pangandaran Regency. The targets attended were 40 people at face to face meeting, and 260 people at online meeting. The meeting was located at Grand Mutiara Pangandaran Hotel hall. The materials presented including three topics i.e. 1) Social Media-Based Teaching Materials, 2) Digital Applications for Sundanese Language Learning, and 3) Evaluation of Authentic Learning. The results of this community services are 1) the targets gain knowledge on how to manage Sundanese language learning in the 21st century by utilizing modern technology; 2) the targets have skills to select and compile authentic materials and their evaluation in accordance with competency basis and competency core as well as the students needs at every level of education.